Transforming Islamic Education for Environmental and Social Sustainability - Hajar, Andi (Sinergi International Journal of Islamic Studies, 2024)
This study explores the contributions of Islamic education to sustainable development by reviewing recent literature on curriculum innovation, environmental awareness, institutional engagement, and technological adaptation. The aim is to assess how Islamic educational institutions integrate sustainability principles through religious values and pedagogical strategies. Using a narrative review approach, literature from Scopus and Google Scholar was analyzed based on keywords such as "Islamic education," "sustainable development," "green campus," and "Islamic environmental ethics." The study adopts an Islamic ethical framework rooted in the principles of khalifah (stewardship), maslahah (public benefit), and adl (justice), which inform the integration of sustainability into educational models. It focuses primarily on Southeast Asia and the Middle East, analyzing case studies from Indonesia, Saudi Arabia, and other Muslim-majority countries. Findings reveal that Islamic boarding schools (pesantren) in Indonesia have pioneered ecological education through initiatives like Eco-Pesantren, while universities have begun implementing SDG-based curricula and eco-friendly infrastructure. These practices demonstrate the transformative potential of aligning faith-based education with global sustainability goals. However, challenges remain, including limited policy clarity, resource constraints, and the need for standardized evaluation methods. These findings underscore the urgent need for policy reforms, community empowerment, and inter-sectoral collaboration. The study concludes that Islamic education, if strategically supported, can be a powerful force in advancing global sustainability, offering both ethical guidance and practical solutions.